"That Eternal Language," or Why Coleridge was Right about Imaging and Meaning - Reid, Nicholas (Romanticism on the Net)

(untitled) (Université de Montréal, 2002)
AbstractOne of the common mysteries of art, and a barrier to our understanding of Coleridge's claim that natural form lies at the heart of knowledge, is the problem of how it is that art can embody meaning in its sensuous forms—for instance, in visual, tactile or auditory "images." To our common way of thinking, this seems mysterious, for we usually think of thinking as something which is propositional and linguistic, or (though less popular these days) as being in some sense "pure" and above both the senses and language. But while propositional thinking is certainly a dimension of our mental experience, we should not let it blind us to the more fundamental ways in which we perceive and understand the world through the senses. Thus we should not think of syllogistic argument as the paradigm for thought, as the Anglo-American philosophical world has tended to, nor should we think of thought as paradigmatically linguistic in the way the literary theory of the last thirty years has suggested. Rather, we should find that paradigm in those moments when we are looking at the world (looking out of the window at a tree, for instance). Concrete sensuous form, or image, I shall argue, provides a more fundamental paradigm for thought—a paradigm which art brings to the fore, and which is also fundamentally Coleridgean.